Exchange rate regimes and the international transmission of business cycles: Capital account openness matters. (October 2018) - Kim, Kyunghun; Pyun, Ju Hyun
Highlights: Capital openness influences the exchange-rate regime effect on output co-movement. Fixed regimes with high openness are more vulnerable to the US crisis shock. US dollar peggers with low capital openness are insulated from the crisis shock. Abstract: We investigate the role of exchange rate regimes in the international transmission of business cycles during the global financial crisis. We find that exchange rate regimes alone did not account for differences in the international transmission of business cycles during the crisis. However, analysis considering capital account openness and countries with currencies pegged to the U.S. dollar indicates that exchange rate regimes play an important role in shaping business cycle co-movement: adopting a fixed regime with high capital account openness (additionally) increased business cycle co-movement with the United States during the crisis, whereas U.S. dollar peggers with relatively restrictive capital accounts during the crisis were not found to affect business cycle transmission.